2010
DOI: 10.1126/scisignal.2000588
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Purinergic Receptor Signaling Is Essential for Macrophage Chemotaxis

Abstract: Chemotaxis, the movement of cells along chemical gradients, is critical for the recruitment of immune cells to sites of inflammation; however, how cells navigate in chemotactic gradients is poorly understood. Here, we show that macrophages navigate in a gradient of the chemoattractant C5a through the release of adenosine triphosphate (ATP) and autocrine "purinergic feedback loops" that involve receptors for ATP (P2Y(2)), adenosine diphosphate (ADP) (P2Y(12)), and adenosine (A2a, A2b, and A3). Whereas macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
192
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(202 citation statements)
references
References 53 publications
8
192
0
2
Order By: Relevance
“…P2Y 12 and P2X 4 receptor activation has been shown to induce migration of ramified microglia, attracting them to regions of high ATP concentrations [148,149]. Studies using peritoneal macrophages in mice have shown that stimulation of P2Y 2 and P2Y 12 receptors induces the formation of lamellipodial membrane protrusions that leads to cell spreading and efficient directional motility of cells [150]. Taken together, these findings support the hypothesis that extracellular nucleotides serve as endogenous danger signals that activate microglia during the innate immune response.…”
Section: P2y 2 Receptors In Glial Cellssupporting
confidence: 60%
“…P2Y 12 and P2X 4 receptor activation has been shown to induce migration of ramified microglia, attracting them to regions of high ATP concentrations [148,149]. Studies using peritoneal macrophages in mice have shown that stimulation of P2Y 2 and P2Y 12 receptors induces the formation of lamellipodial membrane protrusions that leads to cell spreading and efficient directional motility of cells [150]. Taken together, these findings support the hypothesis that extracellular nucleotides serve as endogenous danger signals that activate microglia during the innate immune response.…”
Section: P2y 2 Receptors In Glial Cellssupporting
confidence: 60%
“…76,77 Many of the inflammatory properties of ATP are linked to their stimulation of the P2X 7 R; however, activation of P2X 7 R requires 4100 μM ATP, 74 indicating that 100-200 nM released during cell death is unlikely to activate the P2X 7 R. In fact, this has been supported by studies that showed pannexin-mediated ATP release does not activate P2X 7 R. 78 P2X receptors only engage ATP, while the P2Y receptors, which are implicated in migration, recognize ATP, UTP, and their metabolites. 79 This recognition repertoire can have an important function in cell clearance, as apoptotic cells also release UTP. Furthermore, ATP and UTP can also elicit monocyte migration indirectly by affecting adhesion molecule expression on vascular endothelial cells.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…The co-expression of these enzymes on immune cells has been demonstrated for activated mouse Treg and Th17 cells, 9,10 but untreated human Tregs in the circulation only express low levels of intracellular CD73. 11 Mouse peritoneal macrophages may also co-express these enzymes, 12 whereas healthy non-activated human blood monocytes and macrophages have abundant expression of CD39 but not CD73 on the cell surface. 13,14 Ectonucleotidase expression can be controlled by the microenvironment; e.g., CD39 expression is regulated by IL-27 in ovarian cancer, 15 while CD73 is upregulated by hypoxia on epithelial cells 16 by TGFb on murine leukocytes 17 and by signal-transducer and activator of transcription-3 (STAT3) activation on murine Th17 cells.…”
Section: Introductionmentioning
confidence: 99%